2015
DOI: 10.1016/j.cegh.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemical exposure in induction and evolution of vitiligo: Correlation between duration of exposure and disease, site of exposure and onset, and impact upon avoidance

Abstract: Leucoderma Chemical exposure a b s t r a c t Background: The exogenous oxidants can trigger and lead to progression and chronicity in idiopathic vitiligo similar to chemical leucoderma and contact vitiligo. Aims: The basic objectives of this study were to study chemical exposure history in vitiligo patients and to correlate this with induction or progression of lesions. Methods: This prospective observational study with intervention in the form of avoidance of exposure was conducted at MGM Medical College, Bih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Phenolic derivatives are structurally similar to the melanin precursor tyrosine, and therefore tyrosinase was originally implicated as a mediator of cytotoxicity, Phenolic compounds may be used as depigmenting agents and because they have a similar chemical structure to tyrosine, the substrate of tyrosinase. 37 Kojic acid and total phenols content, add nitrogen source can increase 0.89~0.54; 1.24~2.26 fold, respectively. Inhibition tyrosinase activity also can increase 0.59~1.55 fold ability (Table 1).…”
Section: Determination Of Total Phenolic and Kojic Acid Contentmentioning
confidence: 97%
“…Phenolic derivatives are structurally similar to the melanin precursor tyrosine, and therefore tyrosinase was originally implicated as a mediator of cytotoxicity, Phenolic compounds may be used as depigmenting agents and because they have a similar chemical structure to tyrosine, the substrate of tyrosinase. 37 Kojic acid and total phenols content, add nitrogen source can increase 0.89~0.54; 1.24~2.26 fold, respectively. Inhibition tyrosinase activity also can increase 0.59~1.55 fold ability (Table 1).…”
Section: Determination Of Total Phenolic and Kojic Acid Contentmentioning
confidence: 97%
“…In another study,[ 36 ] we have been able to show that chemical triggering factors play a very significant role in the induction and propagation of vitiligo. History of household chemical exposure and industrial (occupational) chemical exposure were found in 94.6% and 0.4% of the patients, respectively.…”
Section: Chemical Vitiligo and Vitiligo: Interlinkingmentioning
confidence: 97%
“…The mechanism of chemical-induced vitiligo is complex and still not clear. [ 38 39 ] It has been observed that some chemicals such as monobenzyl ether of hydroquinone (MBEH) and 4-tertiary butyl phenol can downregulate microphthalmia-associated transcription factor (MITF) leading to decreased melanin synthesis and thereby initiation of vitiligo. [ 40 ] MBEH was the first chemical known as causing depigmentation and nowadays, MBEH is approved by the US Food and Drug Administration (FDA) and is used therapeutically to complete and accelerate depigmentation to make the skin tone of patients with severe vitiligo uniform.…”
Section: Signalling Pathways In Vitiligomentioning
confidence: 99%